Relationship between Lipid and Blood Glucose Levels with Stroke Risk in Dupak Surabaya - Olivia Herliani; Chenny Andriani Wiyono; Noer Kumala Indahsari (Universitas Wijaya Kusuma Surabaya, 2024)
Background: Stroke is a syndrome characterized by rapidly developing symptoms and/or clinical signs in the form of focal or global brain functional disorders lasting more than 24 hours which are not caused by causes other than vascular. Stroke is the number one cause of disability and the main cause of death in Indonesia (19.42% of total deaths). Dyslipidemia and diabetes mellitus are two-fold risk factors for stroke.This research is to determine the relationship between lipids and blood glucose and a high risk of stroke. Methods: This research uses descriptive analytical methods with a cross sectional approach. The population is residents in Dupak Surabaya. The sampling method is random sampling technique. The total research sample was 53 participants. The statistical test used is Chi Square. Result: Statistical results show that there is no relationship between high cholesterol levels and the risk of stroke and there is a relationship between high triglyceride and blood sugar levels and the risk of stroke.Conclusion:This research concluded that there was a significant relationship between high levels of triglycerides and blood glucose and the risk of stroke and there was no significant relationship between high cholesterol levels and the risk of stroke. This lack of significant association could be due to the heterogeneous population and the presence of previous anti-cholesterol medication.